Inovasi Lembar Aktivitas Siswa (LAS) Untuk Meningkatkan Keterampilan Proses Dalam Pembelajaran IPA Di SMA: Pendekatan Pembelajaran Aktif Dan Konstruktivisme - Ibnu Hakim (https://journal.metanusantara.com/pedagogia, 2024)
Science learning in high school faces challenges in improving students' process skills, such as observation, experimentation, and analysis. One strategy that can be used to improve these skills is to develop Student Activity Sheets (SAS) that are tailored to the context and needs of students. This study aims to develop LAS that is effective in improving science learning process skills in high school. This type of research is a qualitative approach. The main data sources of this study include students and science teachers in several high schools, which were obtained through observation, interviews, and questionnaires. The results showed that the application of LAS specifically designed for science learning can increase students' involvement in learning activities and their ability to develop scientific process skills. A total of 85% of students showed improvement in active participation during experiments and class discussions, while 90% of students felt more engaged and able to understand the material better. Teachers also reported that the LAS helped lead students to apply science concepts in everyday life and strengthen their understanding of the scientific process. These findings indicate that the developed LAS can be an effective tool in improving students' process skills, as well as supporting more meaningful and active science learning at the high school level.